Silicon-based composite anode material and electrochemical device and electronic device comprising the same
Patent Information
- Application Number
- CN202610909211.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-06-23
- Publication Date
- 2026-08-28
AI Technical Summary
[0002]硅材料的理论比容量可达4200mAh/g,能够显著提升电池的能量密度,但其在充放电过程中会发生体积膨胀(>300%),从而导致活性颗粒破碎或电极结构崩塌,以及固态电解质界面(SEI)的持续破裂与再生,不可逆地消耗电解液
本申请以硅材料为内核并在其表面依次设置第一包覆层和第二包覆层形成硅基复合负极材料,第一包覆层中的多酚类化合物中酚羟基能够与金属离子发生络合形成网络结构,一方面增强内核与第二包覆层的层间结合力,另一方面还能促进整体电子传导性能的提升;第二包覆层中电化学活性官能团分解后所形成的孔结构可作为纳米尺度的弹性缓冲空穴,该弹性缓冲空穴能可逆地储存和释放弹性能,并根据内核的膨胀程度而进行动态调整以避免局部应力集中来有效提升硅基复合负极材料的结构稳定性;第二包覆层中电化学活性官能团,还能在充放电过程中硅发生大量锂化之前,优先发生还原反应形成一层致密且富含无机成分的稳定SEI膜;第一包覆层与第二包覆层协同作用,赋予硅基复合负极材料优异的长循环稳定性和高首效。
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] This application relates to the field of electrochemical energy storage technology, and more specifically, to silicon-based composite anode materials and electrochemical and electronic devices comprising the same. Background Technology
[0002] Silicon materials have a theoretical specific capacity of up to 4200 mAh / g, which can significantly improve the energy density of batteries. However, they undergo volume expansion (>300%) during charge and discharge, leading to the breakage of active particles or the collapse of electrode structures, as well as the continuous rupture and regeneration of the solid electrolyte interface (SEI), resulting in irreversible consumption of electrolyte. Currently, these problems are mainly addressed by using physically mixed carbon materials, constructing porous / hollow structures, and elastic polymer coatings. However, these methods still struggle to effectively improve the long-cycle stability and first-efficiency performance of silicon materials simultaneously. Summary of the Invention
[0003] The purpose of this application is to overcome the shortcomings of the prior art and provide a silicon-based composite anode material and an electrochemical and electronic device containing the same.
[0004] To achieve the above objectives, the technical solution adopted in this application is as follows: A first aspect of this application provides a silicon-based composite anode material, comprising a core, a first coating layer located on at least a portion of the surface of the core, and a second coating layer located on at least a portion of the surface of the first coating layer; The core includes at least one of silicon-carbon, elemental silicon, and silicon oxide; The first coating layer comprises polyphenolic compounds and metal ions; The second coating layer comprises a cross-linked polymer having electrochemically active functional groups, wherein the electrochemically active functional groups are functional groups that can decompose and form a porous structure under electrochemical reduction conditions.
[0005] In some embodiments of this application, the molar coordination ratio of the metal ion to the phenolic hydroxyl group in the polyphenol compound is 1:3 to 1:6.
[0006] In some embodiments of this application, the mass ratio of silicon to metal in the silicon-based composite anode material is 100:0.1 to 100:2.
[0007] In some embodiments of this application, the second coating layer has a porous structure; Based on the total mass of the first coating layer, the mass percentage of the metal element is X, in % (%). The effective porosity of the second coating layer is P, in % . X and P satisfy the relationship: 8≤P-8X≤16.
[0008] In some embodiments of this application, the second covering layer has a porous structure, which includes closed pores and semi-closed pores.
[0009] In some embodiments of this application, based on the total pore volume of the pore structure, the volume ratio of the closed pores is ≥60%; and / or, the average pore diameter of the closed pores and / or semi-closed pores is ≤5nm.
[0010] In some embodiments of this application, the electrochemically active functional groups account for 10% to 50% of the total mass of the second coating layer.
[0011] In some embodiments of this application, at least one of the following conditions is met: (1) The average particle size of the kernel is 50 nm to 5000 nm; (2) The average thickness of the first coating layer is 2 nm to 10 nm; (3) The average thickness of the second coating layer is 20 nm to 80 nm; (4) The metal ions in the first coating layer include Fe 3+ Al 3+ Cu 2+ Co 2+ Ni 2+ Zn 2+ Mn 2+ Zr 4+ Ti 4+ At least one of them; (5) The crosslinked polymer in the second coating layer comprises structural units derived from at least one of fluorinated (meth)acrylate monomers, olefin monomers containing lithium sulfonate groups, and cyclic carbonate derivatives containing unsaturated bonds.
[0012] A second aspect of this application provides an electrochemical device comprising the silicon-based composite anode material provided in the first aspect of this application.
[0013] A third aspect of this application provides an electronic device that includes the electrochemical device provided in the second aspect of this application.
[0014] Compared with the prior art, the beneficial effects of this application are as follows: This application uses silicon material as the core and sequentially deposits a first coating layer and a second coating layer on its surface to form a silicon-based composite anode material. The phenolic hydroxyl groups in the polyphenolic compounds in the first coating layer can complex with metal ions to form a network structure, which enhances the interlayer bonding force between the core and the second coating layer and promotes the overall electronic conductivity. The porous structure formed by the decomposition of electrochemically active functional groups in the second coating layer can serve as nanoscale elastic buffer holes. These elastic buffer holes can reversibly store and release elastic energy and dynamically adjust according to the expansion degree of the core to avoid local stress concentration and effectively improve the structural stability of the silicon-based composite anode material. The electrochemically active functional groups in the second coating layer can also preferentially undergo reduction reactions before silicon undergoes a large amount of lithiation during charging and discharging to form a dense and inorganic-rich stable SEI film. The synergistic effect of the first and second coating layers endows the silicon-based composite anode material with excellent long-cycle stability and high first-efficiency. Detailed Implementation
[0015] To better illustrate the purpose, technical solution, and advantages of this application, the following detailed description, in conjunction with specific embodiments, aims to explain the content of this application in detail, rather than to limit it. All other embodiments obtained by those skilled in the art without inventive effort are within the protection scope of this application.
[0016] <General Definition> The term "silicon-carbon" refers to composite materials containing silicon and carbon elements. Specific forms include, but are not limited to: nano-silicon-carbon composites, silicon / carbon core-shell structures, silicon oxide / carbon composites, porous silicon / carbon composites, and materials formed by combining silicon-based materials with carbon materials (such as graphite, soft carbon, hard carbon, carbon nanotubes, graphene, etc.) through methods such as vapor deposition, mechanical ball milling, and high-temperature pyrolysis.
[0017] The term "polyphenolic compounds" refers to a class of compounds whose molecular structure contains two or more phenolic hydroxyl groups (-OH). A key characteristic of these compounds is that the phenolic hydroxyl groups can undergo coordination complexation reactions with metal ions to form a stable three-dimensional network structure. In this application, the polyphenolic compounds are preferably tannic acid, dopamine, and their derivatives, but are not limited to these, and also include other naturally extracted or artificially synthesized compounds containing catechol or pyrogallol structures.
[0018] The term "crosslinked polymer" refers to a polymer with a three-dimensional network or bulk structure formed by linear or branched polymer molecular chains interconnected by chemical bonds (covalent or ionic bonds). Compared to linear polymers, crosslinked polymers exhibit better mechanical strength, structural stability, and solvent resistance. In this application, the crosslinked polymer of the second coating layer is formed by reacting polymeric monomers through free radical polymerization or other methods in the presence of a crosslinking agent. Its three-dimensional network structure helps provide a stable framework and provides a basis for the formation of the pore structure.
[0019] The term "closed pore" refers to a porous structure that is completely surrounded by a polymer matrix and has no communication path with the external environment (including the electrolyte). In this application, the closed pores in the second coating layer are similar to independent "nanosprings" that can be compressed to store elastic energy when the silicon core expands and release elastic energy when it contracts, thereby efficiently buffering volume changes. Furthermore, because they are isolated from the electrolyte, no SEI film will form inside them.
[0020] The term "semi-closed pore" refers to a pore structure with an opening, but the opening size is extremely small (typically smaller than the Stokes diameter of solvated lithium ions). Although such pores are physically connected to the outside, due to size limitations, solvated lithium ions in the liquid electrolyte cannot effectively penetrate into the pore interior. In this application, the semi-closed pore essentially plays a buffering role similar to a closed pore during electrochemical cycling, providing deformation space and limiting the formation area of the SEI film to the outer surface of the material, thus avoiding irreversible consumption of the lithium source due to internal film formation.
[0021] In the following description, all figures disclosed in this application are approximations.
[0022] Throughout this specification, references to “implementation,” “partial implementation,” “one implementation,” “another enumerated method,” “specific method,” or “partial method” mean that at least one implementation or embodiment in this application includes the specific features, structures, materials, or characteristics described in that implementation or embodiment.
[0023] I. Silicon-based composite anode materials This application provides a silicon-based composite anode material, which includes a core, a first coating layer located on at least a portion of the surface of the core, and a second coating layer located on at least a portion of the surface of the first coating layer; The core includes at least one of silicon-carbon, elemental silicon, and silicon oxide; The first coating layer comprises polyphenolic compounds and metal ions; The second coating layer comprises a cross-linked polymer having electrochemically active functional groups, wherein the electrochemically active functional groups are functional groups that can decompose and form a porous structure under electrochemical reduction conditions.
[0024] This application uses silicon material as the core and sequentially deposits a first coating layer and a second coating layer on its surface to form a silicon-based composite anode material. The phenolic hydroxyl groups in the polyphenolic compounds in the first coating layer can complex with metal ions to form a network structure, which enhances the interlayer bonding force between the core and the second coating layer and promotes the overall electronic conductivity. The porous structure formed by the decomposition of electrochemically active functional groups in the second coating layer can serve as nanoscale elastic buffer holes. These elastic buffer holes can reversibly store and release elastic energy and dynamically adjust according to the expansion degree of the core to avoid local stress concentration and effectively improve the structural stability of the silicon-based composite anode material. The electrochemically reducing active functional groups in the second coating layer can also preferentially undergo a reduction reaction before silicon undergoes a large amount of lithiation during charging and discharging to form a dense and inorganic-rich stable SEI film. The synergistic effect of the first and second coating layers endows the silicon-based composite anode material with excellent long-cycle stability and high first-efficiency.
[0025] In some embodiments, the polyphenolic compound in the first coating layer is preferably at least one of tannic acid and dopamine.
[0026] In some embodiments, the metal ions in the first coating layer are preferably multivalent metal ions, including but not limited to Fe. 3+ Al 3+ Cu 2+ Co 2+ Ni 2+ Zn 2+ Mn 2+ Zr 4+ Ti 4+ At least one of them.
[0027] In some embodiments, the molar coordination ratio of the metal ion to the phenolic hydroxyl group in the polyphenolic compound is 1:3 to 1:6, for example, but not limited to 1:3, 1:3.1, 1:3.2, 1:3.3, 1:3.4, 1:3.5, 1:3.6, 1:3.7, 1:3.8, 1:3.9, 1:4, 1:4.1, 1:4.2, 1:4.3, 1:4.4, 1:4.5, 1:4.6, 1:4.7, 1:4.8, 1:4.9, 1:5, 1:5.1, 1:5.2, 1:5.3, 1:5.4, 1:5.5, 1:5.6, 1:5.7, 1:5.8, 1:5.9, or 1:6, or falls within the range of any two of the above values.
[0028] By controlling the molar coordination ratio of metal ions to phenolic hydroxyl groups in polyphenolic compounds within the above-mentioned range, it is more conducive to the formation of a continuous, uniform, and flexible three-dimensional network framework between metal ions and phenolic hydroxyl groups in polyphenolic compounds. This not only enhances the adhesion of the first coating layer and reduces the risk of interfacial peeling from the core during charging and discharging, but also provides an effective "jump station" for electron transport to reduce interfacial impedance. At the same time, it can better adapt to the volume changes of the core without becoming brittle, providing stable mechanical support for the second coating layer, improving the uniformity and bonding strength of the second coating layer, and thus better improving the cycle stability and first-time efficiency of silicon-based composite anode materials.
[0029] In some embodiments, the mass ratio of silicon to metal in the silicon-based composite anode material is from 100:0.1 to 100:2, for example, but not limited to 100:0.1, 100:0.2, 100:0.3, 100:0.4, 100:0.5, 100:0.6, 100:0.7, 100:0.8, 100:0.9, 100:1, 100:1.1, 100:1.2, 100:1.3, 100:1.4, 100:1.5, 100:1.6, 100:1.7, 100:1.8, 100:1.9 or 100:2, or within the range of any two of the above values.
[0030] By controlling the mass ratio of silicon to metal elements in the silicon-based composite anode material within the aforementioned range, not only can the number of metal ions better match the phenolic hydroxyl groups in polyphenolic compounds to form a stable coordination complex structure, promoting the self-assembly of a uniform, continuous, and dense complex network on the core surface to optimize electron / ion transport paths and enhance interface stability, but it can also effectively prevent metal ions from precipitating in the form of metal oxide / hydroxide clusters, which would cause the first coating layer to become brittle and prone to cracking. Simultaneously, it can suppress the formation of metal-rich regions to ensure rapid lithium-ion transport. Furthermore, it helps reduce free metal ions, preventing them from undergoing reduction precipitation or catalyzing side reactions in the electrolyte during electrochemical processes, thereby better improving the cycle stability and first-time efficiency of the silicon-based composite anode material.
[0031] The mass ratio of silicon to metal in silicon-based composite anode materials can be determined by the following method: inductively coupled plasma mass spectrometry (ICP-MS) can be used to determine the mass content of silicon and the mass content of metal, and then the mass ratio of silicon to metal can be calculated.
[0032] In some embodiments, the second coating layer has a porous structure; Based on the total mass of the first coating layer, the mass percentage of the metal element is X, in % (%). The effective porosity of the second coating layer is P, in % . X and P satisfy the relationship: 8≤P-8X≤16.
[0033] In some implementations, the value of P-8X may be, but is not limited to, 8, 8.5, 9, 9.5, 10, 10.5, 11, 11.5, 12, 12.5, 13, 13.5, 14, 14.5, 15, 15.5 or 16, or fall within the range of any two of the above values.
[0034] By adjusting the value of P-8X within the above range, it is more conducive to the synergistic effect of the first coating layer and the second coating layer. This not only better leverages the buffering effect of the second coating layer on volume expansion, but also better improves the electronic conductivity of the silicon-based composite material, further enhancing the long-cycle stability and first-efficiency of the silicon-based composite anode material.
[0035] In some implementations, the value of X ranges from 1% to 10%, for example, it can be, but is not limited to, 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, or 10%, or it can be within the range of any two of the above values.
[0036] By controlling the mass ratio X of the metal element in the first coating layer within the above range, it is possible not only to better promote the full coordination and cross-linking of phenolic hydroxyl groups in polyphenolic compounds with metal ions, forming a continuous electronic conduction pathway on the surface of the core and reducing interfacial contact resistance, but also to effectively prevent metal ions from precipitating in the form of metal oxide or hydroxide clusters, reducing the generation of cracks or local defects in the first coating layer, improving the structural stability of the first coating layer during charge-discharge cycles, and thus better enhancing the long-cycle stability and first-time efficiency of silicon-based composite anode materials.
[0037] In some implementations, the value of P ranges from 16% to 80%, preferably from 30% to 60%, for example, but not limited to 16%, 20%, 25%, 30%, 35%, 40%, 45%, 50%, 55%, 60%, 65%, 70%, 75% or 80%, or falls within the range of any two of the above values.
[0038] By adjusting the effective porosity P of the second coating layer within the above range, not only can sufficient buffer space be provided for the volume expansion of the core to reduce the expansion rate of the electrode, but it is also beneficial to form a stable SEI film on the surface of the second coating layer to reduce the continuous consumption of active lithium and electrolyte. At the same time, it can also effectively prevent ion transport from being interrupted by too many pores, which would lead to an increase in interfacial impedance.
[0039] Effective porosity (P) refers to the percentage of the total volume of the second coating layer that is open to the external environment or can be entered by probe molecules (such as nitrogen).
[0040] The pore structure of the second coating layer includes closed pores and semi-closed pores, but the effective porosity only includes pores with a connection to the outside (i.e., open pores, including semi-closed pores and through pores). Closed pores are not included in the effective porosity because they are not connected to the outside. Specifically, the gas adsorption method (nitrogen adsorption) combined with the BJH model can be used to determine the open pore volume of the intermediate pores (2~50nm) in the second coating layer, and then the effective porosity can be calculated by combining it with the total volume of the second coating layer.
[0041] Specifically, the steps include: (1) Sample pretreatment: Take an appropriate amount of silicon-based composite anode material powder and dry it in a vacuum drying oven at 60℃ for 12 hours to remove surface-adsorbed moisture and volatile substances. Transfer the dried sample to a degassing station and dry it at 150℃ and a vacuum degree <10. -3 Degassing under Pa conditions for 6 hours to completely remove impurity gases from the pores.
[0042] (2) Nitrogen adsorption isotherm determination: Static volumetric adsorption analysis was performed using a specific surface area and pore size analyzer (Micromeritics ASAP 2460) with high-purity nitrogen (≥99.999%) as the adsorbate at liquid nitrogen temperature (77.3 K). Relative pressure (P / P0) test points were set: 10 points in the low-pressure region (0.005~0.1) and 20 points in the high-pressure region (0.1~0.995), simultaneously measuring the adsorption and desorption branches. The amount of nitrogen adsorbed (cm³) at each relative pressure was recorded. 3 / g STP).
[0043] (3) Aperture distribution and opening volume calculation: The desorption branch (or adsorption branch, selected according to the hysteresis loop type) of the nitrogen adsorption isotherm was analyzed using the Barrett-Joyner-Halenda (BJH) model. The cumulative pore volume in the pore size range of 2–50 nm was calculated and denoted as Vmeso (unit: cm). 3 / g). This volume corresponds to the total volume of the pores (including semi-closed pores and through pores) in the second coating layer.
[0044] In this application, the average pore size of the closed and semi-closed pores in the second coating layer is ≤5nm. Therefore, the pore volume in the range of 2~5nm is the main contributor to the effective porosity. The BJH model has good accuracy within this pore size range.
[0045] (4) Determination of the total volume of the second coating layer: The total volume of the second coating layer needs to be calculated using transmission electron microscopy (TEM) combined with image analysis. High-resolution TEM images are taken after embedding the silicon-based composite anode material, slicing it into ultrathin sections, and then randomly selecting at least 50 particles. The average thickness (t, unit: nm) of the second coating layer and the particle core radius (r, unit: nm) of each particle are measured. The volume of the second coating layer of a single particle is then V. shell =43π[(r+t) 3 -r 3 After statistical averaging, and considering the number and density of particles, the total volume V of the second coating layer per unit mass of sample is calculated. total (Unit: cm) 3 / g).
[0046] (5) Calculation of effective porosity: P = Vmeso / Vtotal × 100%.
[0047] In some embodiments, the second coating layer has a porous structure, which includes closed pores and semi-closed pores.
[0048] The closed pores in the second coating layer act like independent "nanosprings," reversibly storing and releasing elastic energy to achieve high buffering efficiency. Although the semi-closed pores have open pores, the size of the open pores is smaller than the Stokes diameter of the solvated lithium-ion complex in conventional liquid electrolytes. Thus, during electrochemical cycling, they substantially hinder or significantly delay the wetting and filling of the pores by the liquid electrolyte bulk. In other words, the semi-closed pores can also play the same buffering role as the closed pores.
[0049] In some embodiments, based on the total hole volume of the hole structure, the volume ratio of the closed hole is ≥60%, preferably 70% to 90%, for example, but not limited to 60%, 62%, 64%, 66%, 68%, 70%, 72%, 74%, 76%, 78%, 80%, 82%, 84%, 86%, or 90%, or within the range of any two of the above values.
[0050] By controlling the volume ratio of closed pores within the above range, it is more conducive to inhibiting the formation of continuous permeation pathways in semi-closed pores, thereby effectively blocking the overall wetting of the pore network by the electrolyte, and reducing the consumption of additives and solvents in the electrolyte due to excessive SEI membrane formation, thus retaining sufficient electrolyte for subsequent cycles.
[0051] The volume ratio of closed pores in the pore structure of the second coating layer in silicon-based composite anode materials can be determined by gas adsorption combined with mercury porosimetry. First, the total pore volume of the pore structure is determined using an automated mercury porosimetry instrument (Micromeritics AutoPore IV series). Then, the volume of open pores (semi-closed pores + through pores) is determined using a surface area and pore size analyzer (Micromeritics ASAP 2460). The volume ratio of closed pores = (total pore volume - open pore volume) / total pore volume × 100%.
[0052] When determining the volume of open pores (semi-closed pores + through pores), the BJH (Barrett-Joyner-Halenda) model was used to calculate the mesopore size distribution, and the pore volume in the range of 2~50nm was accumulated. Since the average pore size of closed and semi-closed pores in this application is ≤5nm, the BJH model has good accuracy in this range.
[0053] In some embodiments, the average pore diameter of the closed and / or semi-closed pores is ≤5nm.
[0054] By controlling the average pore size of the closed and / or semi-closed pores within the aforementioned range, it is possible not only to effectively suppress electrolyte penetration into the pores of the second coating layer, thereby reducing the contact area between the electrode and the electrolyte and minimizing the irreversible consumption of active lithium due to excessive SEI film formation, thus improving the battery's initial efficiency and reducing interfacial impedance; it also helps maintain the overall mechanical strength of the second coating layer, improving its structural stability during charge and discharge processes, providing effective elastic support, and enhancing the buffering effect against expansion stress; simultaneously, it also helps the cross-linked polymers in the second coating layer maintain a continuous conductive network and reduce structural defects in the second coating layer, thereby achieving synergistic optimization of the long-cycle stability and high initial efficiency of the silicon-based composite anode material.
[0055] The average pore diameter of the closed and / or semi-closed pores described in this application was primarily determined by obtaining images of the second coating layer cross-section using a high-resolution transmission electron microscope (HR-TEM). Image analysis software (such as Digital Micrograph or ImageJ) was then used to randomly select at least 50 clearly identifiable pore structures, measuring their maximum and minimum diameters, and taking the average as the pore diameter of a single pore. All measured pore diameter data were statistically averaged to obtain the number-average pore diameter of the sample. Simultaneously, the shape of the pores was observed (closed pores appear as completely closed circles or ellipses, while semi-closed pores appear as cup-shaped or semi-circular pores with one open end) to aid in determining the pore type.
[0056] In some embodiments, the electrochemically active functional groups account for 10% to 50% of the total mass of the second coating layer, preferably 20% to 40%, for example, but not limited to 10%, 12%, 14%, 16%, 18%, 20%, 22%, 24%, 26%, 28%, 30%, 32%, 34%, 36%, 38%, 40%, 42%, 44%, 46%, 48%, or 50%, or within the range of any two of the above values.
[0057] Electrochemically active functional groups can undergo irreversible chemical decomposition under electrochemical conditions below the silicon-lithium alloying plateau potential, and completely detach from the polymer network in gaseous or volatile small molecule form. The main products of the cleavage are gaseous or small molecules with boiling points below 80°C (such as CO2, isobutylene, formaldehyde, and acetaldehyde), which can be removed from the electrode. After cleavage, the chemical groups remaining in situ are electrochemically inert polar groups, including but not limited to primary / secondary amino groups (-NH2 / -NHR), hydroxyl groups (-OH), and carboxylic acid (salt) groups (-COO). - Li + ).
[0058] Polar groups (such as -COO) - Li + -OLi is a good lithium-ion conductor or solvent, which can reduce charge transfer resistance (Rct) and improve the rate performance and low-temperature performance of the battery.
[0059] Preferably, the electrochemically active functional group is derived from (meth)acrylate monomers with easily deprotected groups such as tert-butyloxycarbonyl (Boc), acetal, orthoester group.
[0060] In some embodiments, the average particle size of the core is 50 nm to 5000 nm, preferably 100 nm to 1000 nm, for example, but not limited to 50 nm, 100 nm, 200 nm, 300 nm, 400 nm, 500 nm, 600 nm, 700 nm, 800 nm, 900 nm, 1000 nm, 1500 nm, 2000 nm, 2500 nm, 3000 nm, 3500 nm, 4000 nm, 4500 nm or 5000 nm, or within the range of any two of the above values.
[0061] By controlling the average particle size of the core within the above range, not only can the energy density and expansion stress of the silicon-based composite anode material be better balanced, but the synergistic effect of the first coating layer and the second coating layer can also be better promoted. While the first coating layer forms a continuous electron conduction pathway, the elastic buffer space of the second coating layer is matched with the size change after the core expands to achieve efficient stress release, thereby better improving the long-cycle stability and high first-efficiency of the silicon-based composite anode material.
[0062] In some embodiments, the average thickness of the first coating layer is 2 nm to 10 nm, preferably 3 nm to 5 nm, for example, but not limited to 2 nm, 3 nm, 4 nm, 5 nm, 6 nm, 7 nm, 8 nm, 9 nm or 10 nm, or within the range of any two of the above values.
[0063] By controlling the average thickness of the first coating layer within the aforementioned range, it is not only more conducive to the formation of hydrogen bonds or chemical adsorption between the phenolic hydroxyl groups in the polyphenolic compounds and the hydroxyl groups on the surface of the silicon-based core, and coordination with metal ions, thereby firmly anchoring the first coating layer to the core surface, but also to the formation of a continuous conductive network to provide an effective transport channel for electrons to reduce interfacial impedance. At the same time, it can also serve as a transition layer to better promote the deposition and adhesion of the second coating layer, and uniformly transfer the stress generated by the expansion of the silicon-based core to the second coating layer, thereby better realizing the transfer and dissipation of stress. In addition, it is also conducive to enhancing the bonding force between the second coating layer and the core, avoiding interlayer delamination of the double-layer coating structure during the repeated expansion / contraction of the core, thereby significantly improving the long-cycle stability and high first-efficiency of the silicon-based composite anode material.
[0064] In some embodiments, the average thickness of the second coating layer is 20 nm to 80 nm, preferably 30 nm to 50 nm, for example, but not limited to 20 nm, 25 nm, 30 nm, 35 nm, 40 nm, 45 nm, 50 nm, 55 nm, 60 nm, 65 nm, 70 nm, 75 nm or 80 nm, or within the range of any two of the above values.
[0065] By controlling the average thickness of the second coating layer within the aforementioned range, it is possible not only to accommodate a sufficient number of nanopores to form an effective "nanospring" array and dynamically adjust according to the degree of core expansion to achieve efficient stress release, but also to ensure the smooth diffusion of lithium ions and enable the second coating layer to have good mechanical strength to withstand repeated volume changes without breaking, thereby better leveraging the elastic buffering effect of the second coating layer.
[0066] In some embodiments, the metal ions in the first coating layer include polyvalent metal ions, which can form stable coordination complex structures with the phenolic hydroxyl groups in polyphenolic compounds.
[0067] In some embodiments, the metal ion may be selected from Fe. 3+ Al 3+ Cu 2+ Co 2+ Ni 2+ Zn 2+ Mn 2+ Zr 4+ Ti 4+ At least one of them.
[0068] Preferably, the metal ion is Fe. 3+ Al 3+ Cu 2+ Co 2+ or Ni 2+ These metal ions have a strong coordination ability with polyphenolic compounds, forming a stable complex network structure with good electronic conductivity, which can better realize the function of the first coating layer.
[0069] In some embodiments, the crosslinked polymer in the second coating layer comprises structural units derived from at least one of fluorinated (meth)acrylate monomers, olefin monomers containing lithium sulfonate groups, and cyclic carbonate derivatives containing unsaturated bonds.
[0070] Fluorinated alkyl groups (such as -CF3, -CF2-) release fluoride ions during reduction, which combine with lithium ions to form LiF, a high-interfacial-energy, highly chemically stable material. LiF is a key component in high-quality SEI films, significantly improving their density and mechanical strength. Lithium sulfonate groups (such as -SO3Li) produce lithium sulfate and lithium sulfite as reduction products. These components have good lithium-ion conductivity, helping to reduce the impedance of the SEI film and participating in the construction of a stable inorganic interface layer. Unsaturated carbonate groups (such as vinylene carbonate groups) contain carbon-carbon double bonds and cyclic carbonate structures, exhibiting high electrochemical reduction activity. They can undergo ring-opening polymerization, forming a flexible polymer protective layer on the electrode surface, filling the gaps between inorganic SEI components.
[0071] In some embodiments, the second coating layer is formed by in-situ polymerization of polymeric monomer A, polymeric monomer B and crosslinking agent, wherein the mass ratio of polymeric monomer A, polymeric monomer B and crosslinking agent is (5~10):(1~5):(0.1~1).
[0072] In some embodiments, the polymeric monomer A includes, but is not limited to, at least one of (tert-butoxycarbonylamino)ethyl methacrylate, methyl methacrylate, acrylonitrile, styrene, glycidyl methacrylate, and hydroxyethyl methacrylate.
[0073] In some embodiments, the polymeric monomer B includes, but is not limited to, at least one of trifluoroethyl methacrylate, 2-acrylamide-2-methylpropanesulfonic acid, vinylene carbonate, vinyl ethylene carbonate, acrylic acid, methacrylic acid, lithium p-styrenesulfonate, and lithium methacrylate.
[0074] In some embodiments, the crosslinking agent includes, but is not limited to, at least one of polyethylene glycol diacrylate, divinylbenzene, N,N'-methylenebisacrylamide, ethylene glycol dimethacrylate, trimethylolpropane triacrylate, and pentaerythritol tetraacrylate.
[0075] In some embodiments, the average molecular weight of polyethylene glycol diacrylate is 600 to 10,000.
[0076] <Preparation of Silicon-based Composite Anode Materials> S1. Disperse silicon material particles in an aqueous solution of polyphenolic compound, mix evenly, add soluble metal salt solution to react, centrifuge, wash and dry to obtain silicon material with coating layer; S2. Mix the coated silicon material, polymer monomer A, polymer monomer B, crosslinking agent, initiator and solvent evenly, react at 40°C to 80°C for 4 to 24 hours, wash and dry to obtain intermediate product. S3. The intermediate product is heat-treated in an inert gas atmosphere at 80°C to 150°C for 1 to 5 hours to obtain a silicon-based composite anode material.
[0077] In some embodiments, the mass ratio of polymeric monomer A, polymeric monomer B and crosslinking agent is (5~10):(1~5):(0.1~1).
[0078] In some embodiments, the polymeric monomer A includes, but is not limited to, at least one of (tert-butoxycarbonylamino)ethyl methacrylate, methyl methacrylate, acrylonitrile, styrene, glycidyl methacrylate, and hydroxyethyl methacrylate.
[0079] In some embodiments, the polymeric monomer B includes, but is not limited to, at least one of trifluoroethyl methacrylate, 2-acrylamide-2-methylpropanesulfonic acid, vinylene carbonate, vinyl ethylene carbonate, acrylic acid, methacrylic acid, lithium p-styrenesulfonate, and lithium methacrylate.
[0080] In some embodiments, the crosslinking agent includes, but is not limited to, at least one of polyethylene glycol diacrylate, divinylbenzene, N,N'-methylenebisacrylamide, ethylene glycol dimethacrylate, trimethylolpropane triacrylate, and pentaerythritol tetraacrylate.
[0081] In some embodiments, the initiator includes, but is not limited to, at least one of azobisisobutyronitrile, benzoyl peroxide, potassium persulfate, ammonium persulfate, azobisisobutyronitrile, and lauroyl peroxide.
[0082] II. Electrochemical Device This application provides an electrochemical device, including any apparatus in which an electrochemical reaction occurs to interconvert chemical energy and electrical energy. Specific, non-limiting examples include all types of primary batteries, secondary batteries, fuel cells, solar cells, or capacitors. In particular, the electrochemical device is a lithium secondary battery, including lithium metal secondary batteries, lithium-ion secondary batteries, lithium polymer secondary batteries, or lithium-ion polymer secondary batteries.
[0083] In some embodiments, the electrochemical device includes a positive electrode, a negative electrode, an electrolyte, and a membrane located between the positive and negative electrodes, and the membrane used in the electrochemical device is any of the membranes described herein.
[0084] Positive electrode The positive electrode may include a positive electrode current collector and a positive electrode active material layer disposed on at least one side of the positive electrode current collector.
[0085] In some embodiments, the positive current collector is a metal foil or a composite current collector. In some embodiments, the metal foil is an aluminum foil. The composite current collector may include a metal foil substrate and a conductive layer disposed on at least one side of the metal foil substrate.
[0086] In some embodiments, the conductive layer may include at least one of carbon, carbon black, graphite, expanded graphite, graphene, graphene nanosheets, carbon fiber, carbon nanofiber, graphitized carbon sheet, carbon tube, carbon nanotube, activated carbon, and mesoporous carbon.
[0087] In some embodiments, the positive electrode active material layer may include a positive electrode active material, a positive electrode binder, and a positive electrode conductive agent.
[0088] In some embodiments, the positive electrode active material is selected from LiCoO2, LiNiO2, and LiNi x Mn y O2, Li 1+ z Ni x Mn y Co 1-x-y O2, LiNi x Co y Al zThe group consisting of O2, LiV2O5, LiTiS2, LiMoS2, LiMnO2, LiCrO2, LiMn2O4, Li2MnO3, LiFeO2, LiFePO4, LiMnPO4, and combinations thereof, wherein each x is independently 0.2 to 0.9; each y is independently 0.1 to 0.45; and each z is independently 0 to 0.2. The positive electrode active material of this application is not limited to the above-mentioned materials, but also includes other materials that can be used as positive electrode active materials.
[0089] In some embodiments, the positive electrode active material is selected from LiCoO2, LiNiO2, and LiNi x Mn y O2, Li 1+ z Ni x Mn y Co 1-x-y O2, LiNi x Co y Al z The group consisting of O2, LiV2O5, LiTiS2, LiMoS2, LiMnO2, LiCrO2, LiMn2O4, LiFeO2, LiFePO4 and combinations thereof, wherein each x is independently 0.4 to 0.6; each y is independently 0.2 to 0.4; and each z is independently 0 to 0.1.
[0090] In some embodiments, the positive electrode active material is Li 1+x Ni a Mn b Co c Al (1-a-b-c) O2; where -0.2≤x≤0.2, 0≤a<1, 0≤b<1, 0≤c<1 and a+b+c≤1.
[0091] In some embodiments, the positive electrode active material has the general formula Li 1+x Ni a Mn b Co c Al (1-a-b-c)O2, where 0.33≤a≤0.92, 0.33≤a≤0.9, 0.33≤a≤0.8, 0.5≤a≤0.92, 0.5≤a≤0.9, 0.5≤a≤0.8, 0.6≤a≤0.92 or 0.6≤a≤0.9; 0≤b≤0.5, 0≤b≤0.3, 0.1≤b≤0.5, 0.1≤b≤0.4, 0.1≤b≤0.3, 0.1≤b≤0.2 or 0.2≤b≤0.5; 0≤c≤0.5, 0≤c≤0.3, 0.1≤c≤0.5, 0.1≤c≤0.4, 0.1≤c≤0.3, 0.1≤c≤0.2 or 0.2≤c≤0.5.
[0092] In some embodiments, the positive electrode active material is doped with a dopant selected from the group consisting of Fe, Ni, Mn, Al, Mg, Zn, Ti, La, Ce, Sn, Zr, Ru, Si, Ge, and combinations thereof. In some embodiments, the dopant is not Fe, Ni, Mn, Mg, Zn, Ti, La, Ce, Ru, Si, or Ge. In some embodiments, the dopant is not Al, Sn, or Zr.
[0093] In some embodiments, the positive electrode active material may include LiNi. 0.33 Mn 0.33 Co 0.33 O2, LiNiO2, LiNi 0.4 Mn 0.4 Co 0.2 O2, LiNi 0.5 Mn 0.3 Co 0.2 O2, LiNi 0.6 Mn 0.2 Co 0.2 O2, LiNi 0.7 Mn 0.15 Co 0.15 O2, LiNi 0.8 Mn 0.1 Co 0.1 O2, LiNi 0.92 Mn 0.04 Co 0.04 O2, LiNi 0.8 Co 0.15 Al 0.05 At least one of O2.
[0094] In some embodiments, the positive electrode binder includes at least one of polyvinylidene fluoride (PVDF), poly(vinylidene fluoride)-hexafluoropropylene (PVDF-HFP), polytetrafluoroethylene (PTFE), vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer, fluorinated acrylate resin, polyacrylic acid, polyacrylonitrile, polyimide, polyurethane, polyvinyl butyral, polyvinylpyrrolidone (PVP), acrylic acid-acrylonitrile-acrylamide copolymer, and acrylic acid-acrylonitrile-acrylate copolymer. The positive electrode binder of this application is not limited to the above materials, but also includes other materials that can be used as battery positive electrode binders.
[0095] In some embodiments, the positive electrode conductive agent may include at least one of carbon, carbon black, graphite, expanded graphite, graphene, graphene nanosheets, superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon fibers, carbon nanofibers, graphitized carbon sheets, carbon nanotubes, carbon nanotubes, activated carbon, and mesoporous carbon. The positive electrode conductive agent in this application is not limited to the above materials, but also includes other materials that can be used as positive electrode conductive agents in batteries.
[0096] <Negative electrode> The negative electrode may include a negative electrode current collector and a negative electrode active material layer disposed on at least one side of the negative electrode current collector.
[0097] In some embodiments, the negative current collector is a metal foil or a composite current collector. In some embodiments, the metal foil is a copper foil. The composite current collector may include a metal foil substrate and a conductive layer disposed on at least one side of the metal foil substrate.
[0098] In some embodiments, the conductive layer may include at least one of carbon, carbon black, graphite, expanded graphite, graphene, graphene nanosheets, carbon fiber, carbon nanofiber, graphitized carbon sheet, carbon tube, carbon nanotube, activated carbon, and mesoporous carbon.
[0099] In some embodiments, the negative electrode active material may include any of the silicon-based composite negative electrode materials described herein.
[0100] In some embodiments, the negative electrode binder may include at least one of polyacrylic acid, polymethacrylic acid, polyacrylate, polymethacrylate, polyacrylamide, styrene-butadiene rubber, acrylic styrene-butadiene rubber, acrylic acid-acrylonitrile-acrylamide copolymer, acrylic acid-acrylonitrile-acrylate copolymer, acrylonitrile-butadiene rubber, nitrile rubber, acrylonitrile-styrene-butadiene copolymer, acryloyl rubber, butyl rubber, fluororubber, polytetrafluoroethylene, polyvinyl alcohol, polyvinyl acetate, polyepoxychloropropane, polyphosphazene, polyacrylonitrile, polystyrene, latex, acrylic resin, phenolic resin, epoxy resin, carboxymethyl cellulose, hydroxypropyl cellulose, cellulose acetate, cellulose acetate butyrate, cellulose acetate propionate, cyanoethyl cellulose, carboxymethyl chitosan, polyester, polyamide, polyether, polyimide, polycarboxylic acid ester, polycarboxylic acid, polyurethane, alginate, fluorinated polymer, chlorinated polymer, polyvinylidene fluoride, and poly(vinylidene fluoride)-hexafluoropropylene. The negative electrode binder of this application is not limited to the above-mentioned materials, but also includes other materials that can be used as battery negative electrode binders.
[0101] In some embodiments, the negative electrode conductive agent may include at least one of carbon, carbon black, graphite, expanded graphite, graphene, graphene nanosheets, superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon fibers, carbon nanofibers, graphitized carbon sheets, carbon nanotubes, carbon nanotubes, activated carbon, and mesoporous carbon. The negative electrode conductive agent of this application is not limited to the above-mentioned materials, but also includes other materials that can be used as battery negative electrode conductive agents.
[0102] Electrolytes In some embodiments, the electrolyte may include at least one of a gel electrolyte, a solid electrolyte, and a liquid electrolyte.
[0103] In some embodiments, the liquid electrolyte may include a non-aqueous solvent and a lithium salt.
[0104] In some embodiments, the lithium salt may include at least one of LiPF6, LiBF4, LiAsF6, LiClO4, LiB(C6H5)4, LiCH3SO3, LiCF3SO3, LiN(SO2CF3)2, LiC(SO2CF3)3, LiSiF6, LiBOB, and lithium difluoroborate.
[0105] In some embodiments, the non-aqueous solvent may be at least one of carbonate compounds, carboxylic acid ester compounds, and ether compounds.
[0106] In some embodiments, the carbonate compound may include at least one of chain carbonate compounds, cyclic carbonate compounds, and fluorocarbonate compounds.
[0107] In some embodiments, the chain carbonate compound may include diethyl carbonate (DEC), dimethyl carbonate (DMC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), methyl ethyl carbonate (MEC), and combinations thereof.
[0108] In some embodiments, the cyclic carbonate compound may include ethylene carbonate (EC), propylene carbonate (PC), butyl carbonate (BC), vinyl ethylene carbonate (VEC), and combinations thereof.
[0109] In some embodiments, the fluorocarbonate compound may include at least one of fluoroethylene carbonate (FEC), 1,2-difluoroethylene carbonate, 1,1-difluoroethylene carbonate, 1,1,2-trifluoroethylene carbonate, 1,1,2,2-tetrafluoroethylene carbonate, 1-fluoro-2-methylethylene carbonate, 1-fluoro-1-methylethylene carbonate, 1,2-difluoro-1-methylethylene carbonate, 1,1,2-trifluoro-2-methylethylene carbonate, and trifluoromethylethylene carbonate.
[0110] In some embodiments, the carboxylic acid ester compound may include at least one of methyl acetate, ethyl acetate, n-propyl acetate, tert-butyl acetate, methyl propionate, ethyl propionate, propyl propionate, γ-butyrolactone, decanoic acid lactone, valerate lactone, mevalonate lactone, caprolactone, and methyl formate.
[0111] In some embodiments, the ether compound may include dibutyl ether, tetraethylene glycol dimethyl ether, diethylene glycol dimethyl ether, 1,2-dimethoxyethane, 1,2-diethoxyethane, ethoxymethoxyethane, 2-methyltetrahydrofuran, tetrahydrofuran, and combinations thereof.
[0112] In some embodiments, the non-aqueous solvent may also include at least one of dimethyl sulfoxide, 1,2-dioxolane, sulfolane, methyl sulfolane, 1,3-dimethyl-2-imidazolium ketone, N-methyl-2-pyrrolidone, formamide, dimethylformamide, acetonitrile, trimethyl phosphate, triethyl phosphate, trioctyl phosphate, and phosphate esters.
[0113] <Septum> The separator separates the negative and positive electrodes and provides a pathway for lithium-ion migration. The use of the separator is not particularly limited, as long as it is a separator commonly used in lithium-ion secondary batteries. In particular, separators with low resistance to electrolyte ion movement and excellent electrolyte permeability are preferred. Specifically, porous polymer membranes can be used, such as porous polymer membranes formed from polyolefin-based polymers (e.g., ethylene homopolymers, propylene homopolymers, ethylene / butene copolymers, ethylene / hexene copolymers, ethylene / methacrylate copolymers, etc.) or laminated structures with two or more layers. Alternatively, nonwoven fabrics formed from conventional porous nonwoven fabrics (e.g., glass fibers with high melting points, polyethylene terephthalate fibers, etc.) can be used. Furthermore, coated separators containing ceramic components or polymer materials to ensure heat resistance or mechanical strength can be used, and can optionally be used as single-layer or multi-layer structures.
[0114] III. Electronic Devices This application provides an electronic device that includes any of the electrochemical devices described herein.
[0115] The electronic device described in this application is not particularly limited and may be any electronic device known in the prior art.
[0116] The application of the electrochemical device in this application is not particularly limited, and it can be used in any electronic device known in the prior art. According to some embodiments of this application, the electronic device includes, but is not limited to, mobile phones, smartphones, laptops, tablets, wearable devices, smartwatches, smart bracelets, smart glasses, power banks, televisions, game consoles, game controllers, digital cameras, smart speakers, headphones, keyboards, mice, monitors, drones, audio equipment, home appliances, toys, power tools, automobiles, motorcycles, electric bicycles, bicycles, robots, robot dogs, industrial robots, android robots, etc.
[0117] To clearly understand the technical solution of this application, the preparation of the diaphragm and electrochemical device is described below with examples and specific preparation methods. Those skilled in the art will understand that the preparation methods described in this application are merely examples, and any other suitable preparation methods are within the scope of this application.
[0118] <Testing Methods> 1. Cyclic performance test Charge-discharge cycle tests were conducted using coin cell half-cells (CR2032 type) at room temperature (25℃±2℃). The specific steps are as follows: (1) Testing equipment Use either the LAND battery testing system or the NEWAE battery testing system, with the channel current range selected as 10mA or 20mA, and the accuracy not less than 0.1%.
[0119] (2) Test conditions settings Test temperature: 25℃±2℃ constant temperature environment Voltage window: 0.005V to 1.5V (vs. Li + / Li) Charge / discharge modes: Constant current constant voltage charging (CCCV) + Constant current discharging (CC) (3) Testing process ① Standing: Let the assembled button half-cell stand at 25°C for 12 hours to allow the electrolyte to fully wet the electrodes and separator, ensuring a stable open-circuit voltage (OCV).
[0120] ② Initial charge and discharge (formation): Charge at a constant current rate of 0.05C to 0.005V, then charge at a constant voltage of 0.005V until the current drops to 10% of 0.05C (i.e., 0.005C). Record the initial charge capacity (C). ch After charging is complete, let it stand for 5 minutes; then discharge it at a constant current rate of 0.05C to 1.5V, and record the first discharge capacity (C). dis ).
[0121] First Coulomb efficiency (ICE) calculation: ICE=C dis / C ch ×100%.
[0122] ③ Cyclic performance test: Activation phase: After the first charge and discharge, perform 3 cycles at a rate of 0.1C to fully activate the electrode material; Long cycle stage: After activation, long cycle test is carried out at 0.5C rate, and the charging and discharging method is the same as above (constant current constant voltage charging + constant current discharging). Number of cycles: 100. Record parameters: Record the charging capacity, discharging capacity, and coulombic efficiency for each cycle.
[0123] Capacity retention rate calculation: Capacity retention rate of the 100th cycle = Discharge capacity of the 100th cycle / Discharge capacity of the 1st cycle × 100%.
[0124] (4) Number of test samples and data processing At least three parallel cells were tested for each embodiment or comparative example, and the average value was taken as the final result.
[0125] 2. Electrode thickness expansion rate test (1) Testing equipment Micrometer: Accuracy is 0.1μm (Mitutoyo micrometer), zero-point calibration is required before measurement; Flatbed tablet press: used to prepare electrode sheets with uniform thickness; Glove box: filled with argon gas, with water and oxygen content both less than 0.1 ppm, used for disassembling batteries after cycling; Vacuum drying oven: used for drying electrode sheets; Anhydrous dimethyl carbonate (DMC): Used to clean electrolyte residue on the surface of electrodes after cycling.
[0126] (2) Preparation of test samples ① Initial electrode thickness measurement: After the negative electrode is prepared and before the battery is assembled, the thickness of the electrode is measured using a micrometer. At least five different locations on the electrode (usually the center point and points evenly distributed around it) are randomly selected for measurement, and the arithmetic mean is taken as the initial thickness, denoted as T0 (unit: μm).
[0127] Measurements should be taken away from the edge area of the electrode (at least 5 mm from the edge) to avoid the influence of coating edge effects. If the electrode has undergone cold pressing, the initial thickness should be measured after cold pressing.
[0128] ② Battery assembly and cycling: The electrodes with measured initial thickness are assembled into button half-cells or full cells, and subjected to 100 charge-discharge cycles according to the aforementioned "cycle test" method.
[0129] (3) Post-cycle electrode processing and thickness measurement ① Battery disassembly: Transfer the battery, after cycling to the specified number of cycles, to an argon-filled glove box. Carefully disassemble the battery casing and remove the negative electrode. Take care to avoid bending or damaging the electrode, and keep it intact.
[0130] ②Electrode cleaning: Immerse the removed negative electrode in anhydrous dimethyl carbonate (DMC) for approximately 30-60 seconds, gently agitating to remove residual electrolyte and lithium salt from the surface. Remove the electrode and rinse it once with fresh DMC to ensure thorough cleaning. Place the cleaned electrode in the glove box transition chamber and vacuum dry at room temperature for 2-4 hours to allow the DMC to completely evaporate.
[0131] ③Thickness measurement after cycle: After drying, the electrode sheet was removed and its thickness was measured using the same micrometer under the same environmental conditions (25°C). Measurements were taken at the same measurement locations (at least 5 points) as the initial thickness, and the arithmetic mean was taken as the thickness after the cycle, denoted as T1 (unit: μm).
[0132] (4) Calculation of thickness expansion rate Electrode thickness expansion rate = (T1-T0) / T0×100%.
[0133] Example 1 <Preparation of Silicon-based Composite Anode Materials> S1. At room temperature (25℃), 1g of silicon-carbon particles (composed of porous carbon and silicon filling the porous carbon channels, wherein the mass content of silicon is about 50%) were dispersed in an aqueous solution of tannic acid (concentration of 2mg / mL), stirred, and then ferric chloride solution (concentration of 0.1mol / L) was added and reacted for 2h. After centrifugation, washing and drying, Si@TA-Fe particles were obtained. S2. Mix 0.5g of Si@TA-Fe particles, 0.1g of (tert-butyloxycarbonylamino)ethyl methacrylate (i.e., monomer A), 0.9g of trifluoroethyl methacrylate (i.e., monomer B), 0.05g of crosslinking agent (polyethylene glycol diacrylate, with an average molecular weight of 2000) and initiator (0.02g of azobisisobutyronitrile (AIBN)) in a solvent (20mL of tetrahydrofuran (THF)) and stir at 70℃ for 12h. After the reaction is completed, wash and dry to obtain the intermediate product. S3. The intermediate product is heat-treated in N2 atmosphere at 80°C for 3 hours to obtain silicon-based composite anode material.
[0134] <Preparation of the negative electrode> The negative electrode active material (the aforementioned silicon-based composite negative electrode material), conductive agent (Super P), binder (styrene-butadiene rubber), and thickener (sodium carboxymethyl cellulose) are thoroughly mixed in a deionized water solvent system at a mass ratio of 98:0.5:1:0.5 to obtain a negative electrode slurry. The negative electrode slurry is coated onto the negative electrode current collector copper foil, and after drying, cold pressing, and slitting, a negative electrode sheet is obtained.
[0135] <Preparation of the positive electrode> A lithium metal sheet with a diameter of 15.6 mm, a thickness of 0.45 mm, and a purity of 99.9% was selected as the positive electrode.
[0136] <Preparation of Electrolyte> The electrolyte is a 1.0 mol / L LiPF6 solution, in which the lithium salt is LiPF6, the solvent is composed of EC and DEC in a volume ratio of 1:1, and the additive is FEC with a mass fraction of 3% in the electrolyte.
[0137] <Battery Manufacturing> The above-mentioned negative electrode, positive electrode, electrolyte and separator (PE separator) are assembled into a coin cell.
[0138] Examples 2-5 Except for step S1 in the <Preparation of Silicon-based Composite Anode Material> where the amount of ferric chloride solution added is adjusted to make the mass ratio X of the metal element in the first coating layer different from that in Example 1, step S2 where the mass ratio of polymeric monomer A to polymeric monomer B is adjusted, or step S3 where the temperature and time of heat treatment are adjusted to make the effective porosity P of the second coating layer different from that in Example 1, the rest is the same as in Example 1.
[0139] Increasing the mass ratio of monomer A to monomer B, or raising the heat treatment temperature or extending the heat treatment time, can improve the effective porosity P of the second coating layer.
[0140] Example 6 Except for the differences in the average particle size of silicon-carbon particles and the amount of ferric chloride solution added in step S1 of the <Preparation of Silicon-based Composite Anode Material> compared to Example 1, and the differences in the amount of polymer monomer A and polymer monomer B added in step S2, and the stirring reaction at 70°C for 20 hours, the rest are the same as in Example 1.
[0141] Example 7 Except for the differences in the average particle size of silicon-carbon particles and the amount of ferric chloride solution added in step S1 of the <Preparation of Silicon-based Composite Anode Material> compared to Example 1, and the differences in the amount of polymer monomer A and polymer monomer B added in step S2, and the stirring reaction at 55°C for 12 hours, the rest are the same as in Example 1.
[0142] Example 8 Except for replacing silicon carbon particles with silicon nanoparticles with an average particle size of 150 nm, tannic acid aqueous solution with dopamine solution, and ferric chloride solution with zinc chloride solution in step S1 of the <Preparation of Silicon-based Composite Anode Material>, and replacing (tert-butoxycarbonylamino)ethyl methacrylate with methyl methacrylate, trifluoroethyl methacrylate with 2-acrylamide-2-methylpropanesulfonic acid, and polyethylene glycol diacrylate with N,N'-methylenebisacrylamide in step S2, the rest are the same as in Example 1.
[0143] Comparative Example 1 Except for the preparation of silicon-based composite anode materials, which differs from Example 1, the rest is the same as Example 1.
[0144] <Preparation of Silicon-based Composite Anode Materials> S1. At room temperature (25℃), 1g of silicon-carbon particles were dispersed in an aqueous solution of tannic acid (concentration of 2mg / mL), stirred, and then ferric chloride solution (concentration of 0.1mol / L) was added and reacted for 2h. After centrifugation, washing and drying, Si@TA-Fe particles were obtained, which are silicon-based composite anode materials.
[0145] Comparative Example 2 Except for the preparation of silicon-based composite anode materials, which differs from Example 1, the rest is the same as Example 1.
[0146] <Preparation of Silicon-based Composite Anode Materials> S1. Mix 0.5 g of silicon carbon particles, 0.1 g of (tert-butoxycarbonylamino)ethyl methacrylate, 0.9 g of trifluoroethyl methacrylate, 0.05 g of crosslinking agent (polyethylene glycol diacrylate, the same as in Example 1) and initiator (0.02 g of azobisisobutyronitrile (AIBN)) in a solvent (20 mL of tetrahydrofuran (THF)) and stir at 70 °C for 12 h. After the reaction is completed, wash and dry to obtain the intermediate product. S2. The intermediate product is heat-treated in N2 atmosphere at 80°C for 3 hours to obtain silicon-based composite anode material.
[0147] Comparative Example 3 Except for step S2 of the <Preparation of Silicon-based Composite Anode Material>, in which no polymer monomer A is added, the rest is the same as in Example 1.
[0148] Comparative Example 4 Except for step S2 of the <Preparation of Silicon-based Composite Anode Material>, in which no polymer monomer B is added, the rest is the same as in Example 1.
[0149] The specific parameters of the silicon-based composite anode materials in Examples 1-8 and Comparative Examples 1-4 are shown in Tables 1-3, and the performance of the corresponding batteries is shown in Table 4.
[0150] Table 1 Table 2 Table 3 Table 4 According to the data in Table 4, the initial coulombic efficiency of the batteries in Examples 1-8 is ≥81%, and the capacity retention rate after 100 cycles at 0.5C is ≥72%. Furthermore, the electrode thickness expansion rate after 100 cycles is ≤35.8%, indicating that the silicon-based composite anode material of this application possesses both long cycle stability and high initial efficiency. Comparative Examples 1-2 show that if only the first coating layer is applied to the core surface, it is difficult to effectively improve the cycle stability of the battery and suppress the volume expansion of the electrode. If the second coating layer is directly applied to the core surface, it is difficult to form a continuous and effective coating layer, resulting in even worse cycle stability and a higher electrode expansion rate. Comparative Examples 3-4 also reveal that the absence of polymer monomer A or polymer monomer B in the second coating layer makes it difficult to effectively improve the cycle stability of the battery and the electrode expansion rate. In particular, the absence of polymer monomer A prevents the formation of a porous structure in the second coating layer, leading to a significant decrease in battery cycle stability and a substantial increase in electrode expansion rate.
[0151] When the term "embodiment" is mentioned in the specification, it means that there is at least one embodiment in this application that includes the specific feature, structure, material, or characteristic. Therefore, expressions such as "in some embodiments," "in some embodiments," and "exemplary" used throughout the document do not necessarily refer to the same embodiment. Furthermore, the specific feature, structure, material, or characteristic may be combined in any suitable manner in one or more embodiments.
[0152] Although illustrative embodiments have been demonstrated and described, those skilled in the art should understand that the above embodiments should not be construed as limiting the present application, and that changes, substitutions and modifications can be made to the embodiments without departing from the spirit, principles and scope of the present application.
Claims
1. A silicon-based composite anode material, characterized in that, It includes a core, a first covering layer located on at least a portion of the surface of the core, and a second covering layer located on at least a portion of the surface of the first covering layer; The core includes at least one of silicon-carbon, elemental silicon, and silicon oxide; The first coating layer comprises polyphenolic compounds and metal ions; The second coating layer comprises a cross-linked polymer having electrochemically active functional groups, wherein the electrochemically active functional groups are functional groups that can decompose and form a porous structure under electrochemical reduction conditions.
2. The silicon-based composite anode material as described in claim 1, characterized in that, The molar coordination ratio of the metal ion to the phenolic hydroxyl group in the polyphenol compound is 1:3 to 1:
6.
3. The silicon-based composite anode material as described in claim 1, characterized in that, The mass ratio of silicon to metal in the silicon-based composite anode material is from 100:0.1 to 100:
2.
4. The silicon-based composite anode material as described in claim 1, characterized in that, The second coating layer has a porous structure; Based on the total mass of the first coating layer, the mass percentage of the metal element is X, in % (%). The effective porosity of the second coating layer is P, in % . X and P satisfy the relationship: 8≤P-8X≤16.
5. The silicon-based composite anode material as described in claim 1, characterized in that, The second coating layer has a porous structure, which includes closed pores and semi-closed pores.
6. The silicon-based composite anode material as described in claim 5, characterized in that, Based on the total pore volume of the pore structure, the volume ratio of the closed pores is ≥60%; and / or, the average pore diameter of the closed pores and / or semi-closed pores is ≤5nm.
7. The silicon-based composite anode material as described in claim 1, characterized in that, Based on the total mass of the second coating layer, the electrochemically active functional groups account for 10% to 50% of the mass.
8. The silicon-based composite anode material according to any one of claims 1 to 7, characterized in that, At least one of the following conditions must be met: (1) The average particle size of the kernel is 50 nm to 5000 nm; (2) The average thickness of the first coating layer is 2 nm to 10 nm; (3) The average thickness of the second coating layer is 20 nm to 80 nm; (4) The metal ions in the first coating layer include Fe 3+ Al 3+ Cu 2+ Co 2+ Ni 2+ Zn 2+ Mn 2+ Zr 4+ Ti 4+ At least one of them; (5) The crosslinked polymer in the second coating layer comprises structural units derived from at least one of fluorinated (meth)acrylate monomers, olefin monomers containing lithium sulfonate groups, and cyclic carbonate derivatives containing unsaturated bonds.
9. An electrochemical device, characterized in that, Includes the silicon-based composite anode material as described in any one of claims 1 to 7.
10. An electronic device, characterized in that, Includes the electrochemical device as described in claim 9.